Kick Start to an Epidemiological Report of Soccer-Related Craniofacial Trauma Analysis. Issue 4 (17th June 2021) - Nahas, John V.; Choi, Melinda J.; Wolfe, Erin M.; Pierrot, Randall G.; Slavin, Benjamin R.; Plotsker, Ethan L.; Mathew, Prakash J.; Thaller, Seth R.
Abstract : Introduction: Soccer is a global sport played by millions annually with an increasing popularity in the United States. Game is played by a wide range of participants from all ages and levels of competition. This scenario leads to a potential disparity in the injury profile based on quantifiable demographics. As the game continues to grow, injury detection and side-line assessment must change as well. Methods: Utilizing a national injury database, a retrospective cohort study was conducted using 10 years of data collected from randomly selected emergency departments across the United States. Patient demographics, injury sites, and diagnosis were recorded. Diagnoses examined included concussion, contusion or abrasion, dental injury, fracture, hematoma, hemorrhage, internal injury, and laceration. Results: Highest percentage of craniofacial injuries was observed in soccer players between the ages of 12 and 18. In ages 6 to 11 the most common injuries were contusions and dental injuries, with a significantly low number of fractures. Within the age group of 12 to 18 the highest percentage of injuries was concussions. Finally, the highest percentage of injury in the ages of 19 to 34 were fractures and lacerations. Discussion: There is a shift in injury profile as the age of soccer players increases and the level of play becomes faster-paced. In youth players, there is a higher percentage of soft tissue injury. Older players are more likely to suffer a higher degree of injury including fractures, concussions, and lacerations. This suggests a great utility for a layperson-friendly educational intervention initiative applicable to all demographics for the sport of soccer.